Sick to death and not going to take it anymore! : reforming health care for the last years of life - Lynn, Joanne, 1951- (California/Milbank books on health and the public, 2004)
Just a few generations ago, serious illness, like hazardous weather, arrived with little warning, and people either lived through it or died. In this important, convincing, and long-overdue call for health care reform, Joanne Lynn demonstrates that our current health system, like our concepts of health and disease, developed at a time when life was mostly short, serious illnesses and disabilities were common at every age, and dying was quick.